PENGENALAN AUTOMASI PERPUSTAKAAN TERINTEGRASI INLISLITE - Fatmawati, Endang (LIBRARIA : Jurnal Ilmu Perpustakaan dan Informasi, 2020)
This paper describes the basic concepts of library automation based on INLISLite. Although the digital era is the topic of digital libraries, there are also types of libraries that have not been automated. INLISLite as the software was developed by the National Library to make it easier for visitors to get information quickly,precisely, and accurately. INLISLite is an integrated library system software automation application to support the implementation of a digital library network. There are nine modules provided in the INLISLite version 3 application